The economic costs of planting, preserving, and managing the world’s forests to mitigate climate change - K. G. Austin (Nature Portfolio, 2020)
Forests are critical for stabilizing our climate, but costs of mitigation remain uncertain. Here the authors show the global forest sector could reduce emissions by 6.0 GtCO2 yr−1 in 2055, or roughly 10% of the mitigation needed to limit warming to 1.5 °C by mid-century, at a cost of 393 billion USD yr−1, or $281/tCO2.